Chapter L'io nello sguardo dell'altra. L'arte del monologo di Claudio Magris - Biagini, Enza (Biblioteca di Studi di Filologia Moderna, 2021)
The current essay aims to highlighting a few aspects of the fine 'art of the monologue' practiced by Claudio Magris in his remarkable theatrical achievements (three dramatic monologues and two choral plays), in particular, on his most compelling play, Lei dunque capirà (2006). On one hand, the play highlights his masterly use of the stylistic/dialogic capacity of the monologue on stage and, on the other, it offers an unprecedented and extraordinary (parodic) re-actualization of the myth of Orpheus.